(untitled) - Browne, Michael E . (New York, 1998)
Focuses on non-calculus probability theory, making it ideal for humanities and science majors who study practical statistics for problem solving. This popular Schaum's study guide provides new material on descriptive statistics, hi-square distribution, and more.
Keywords: Physics; Problems, exercises, etc